(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2023)
Neoichnology is an actualistic view of how organisms are connected with the place where they live, providing modern models and ideas that serve as analogous. At Chubut province (Patagonia), in the Golfo Nuevo beaches lives a polychaete that inhabits at the same time in rocky abrasion platforms and sandy intertidal sediments. The traces made by the worm can be compared with Caulostrepsis-like in hard substrates while in soft-sediments are comparable with Skolithos- Arenicolites- like structures. The worm builds a “chimney” over the substrate, that can be removed by tidal activity, and incorporated into the surroundings as an “ichnoclast”. The present short note is intended to describe this occurrence and discuss its importance to ichnology.